2004
DOI: 10.1002/ijc.20719
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of serine/threonine kinase Pim‐3 in hepatocellular carcinoma development and its role in the proliferation of human hepatoma cell lines

Abstract: Most cases of human hepatocellular carcinoma develop after persistent chronic infection with human hepatitis B virus or hepatitis C virus, and host responses are presumed to have major roles in this process. To recapitulate this process, we have developed the mouse model of hepatocellular carcinoma using hepatitis B virus surface antigen transgenic mice. To identify the genes associated with hepatocarcinogenesis in this model, we compared the gene expression patterns between pre-malignant lesions surrounded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 52 publications
6
114
0
1
Order By: Relevance
“…Subsequently, Deneen et al (2003) demonstrated that Pim-3 gene transcription was enhanced in the EWS/ETS-induced malignant transformation of NIH 3T3 cells, suggesting the involvement of Pim-3 in tumorigenesis. Consistently, we observed that Pim-3 expression was enhanced in carcinomas but not in normal tissues of human endoderm-derived organs, including the liver (Fujii et al, 2005), pancreas (Li et al, 2006), colon (Popivanova et al, 2007) and stomach (Zheng et al, 2008). Moreover, Pim-3 can inactivate a pro-apoptotic molecule, Bad, and maintain the expression of an anti-apoptotic molecule, Bcl-X L , and prevent apoptosis of human pancreatic cancer and colon cancer cells (Li et al, 2006).…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…Subsequently, Deneen et al (2003) demonstrated that Pim-3 gene transcription was enhanced in the EWS/ETS-induced malignant transformation of NIH 3T3 cells, suggesting the involvement of Pim-3 in tumorigenesis. Consistently, we observed that Pim-3 expression was enhanced in carcinomas but not in normal tissues of human endoderm-derived organs, including the liver (Fujii et al, 2005), pancreas (Li et al, 2006), colon (Popivanova et al, 2007) and stomach (Zheng et al, 2008). Moreover, Pim-3 can inactivate a pro-apoptotic molecule, Bad, and maintain the expression of an anti-apoptotic molecule, Bcl-X L , and prevent apoptosis of human pancreatic cancer and colon cancer cells (Li et al, 2006).…”
Section: Introductionsupporting
confidence: 68%
“…We previously observed that Pim-3 was expressed selectively in pre-malignant and malignant lesions of the mouse HCC model in transgenic mice expressing hepatitis B virus surface antigen (Fujii et al, 2005). Moreover, Pim-3 protein was detected in a substantial proportion of HCC cells and precancerous lesions in human liver samples, but not normal human liver.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations